A bibliometric analysis of medical informatics and telemedicine in sub-Saharan Africa and BRICS nations - Roy Tapera; Yashik Singh (SAGE Publishing, 2021)
The advances in eHealth have dramatically changed the face of healthcare delivery around the world, with Sub-Saharan Africa being no exception. It is essential to identify the prominent, emerging researchers, successful areas of research within the field of Health Informatics (H.I.) and Telemedicine (T.M.) to be duplicated where there is a need. This study gives a bibliometric overview of original research articles on medical informatics and telemedicine indexed in Scopus, PubMed, and Science Direct over the last 20 years in sub-Saharan Africa. Keywords related to health informatics and Telemedicine were used to retrieve relevant literature. We specifically analyzed the evolution, standard metrics, domains of MI and T.M. in sub-Saharan Africa (S.S.A.) and Brazil, Russia, India, China, and South Africa (BRIC) nations. Our results identified mhealth as the main field of research in telemedicine that has seen significant growth in both BRIC and S.S.A nations and is poised to be the focus of research activity in the near future. Research production in mhealth and telemedicine showed a considerable increase from 1999-2018. The production was dominated by articles from South Africa in Africa and China from the BRIC nations. Most prolific authors have resources and are leaders of health informatics projects. The production came from 26 sub-Saharan African countries, denoting this field's devotion in different areas around sub-Sahara. Research in mhealth needs to be encouraged, mostly in the fight against infectious and non-infectious diseases in sub-Saharan Africa, where technology can improve health services and decrease disease burden.